2014
DOI: 10.15560/10.4.857
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of odonate communities within Wadi Sayq, Dhofar Province, Oman (Insecta: Odonata)

Abstract: also exist as Oman's most biodiverse landscape, which was confirmed during our multidisciplinary survey. Materials and MethodsBecause of the difficulty of moving through the rugged terrain of the wadi, survey sites were identified throughout the duration of the 2012 research period, as they were discovered. Eleven sites showed worthwhile populations of Odonata for surveying (figure 1).Site A (16°44′44″ N, 53°13′50″ E; 420 m a.s.l.): Although mostly arid, this area does contain a localised fresh water source cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In summary, the multidisciplinary surveys undertaken by the expeditions, of which this study was a component, revealed high diversity across all taxonomic groups (Ball 2014;Ball et al 2015). When compared to adjacent areas, the monsoon influenced zones of Wadi Sayq have been subject to comparatively low disturbance, likely due to remoteness and inaccessibility.…”
Section: Herpetofauna Of Wadi Sayq Omanmentioning
confidence: 76%
“…In summary, the multidisciplinary surveys undertaken by the expeditions, of which this study was a component, revealed high diversity across all taxonomic groups (Ball 2014;Ball et al 2015). When compared to adjacent areas, the monsoon influenced zones of Wadi Sayq have been subject to comparatively low disturbance, likely due to remoteness and inaccessibility.…”
Section: Herpetofauna Of Wadi Sayq Omanmentioning
confidence: 76%
“…We have recorded each of them except T. tillarga. Tholymis tillarga was added to the Dhofar and Oman lists by Ball (2014), with a record of a male and an ovipositing female in Wadi Sayq, which is close to the Yemeni border, though no ID evidence was presented. Lambret et al (2017) recorded T. tillarga, a record of two individuals on 11 November 2010, at a different site from Ball's (2014), but presented no evidence except "observed at close distance".…”
Section: Discussionmentioning
confidence: 99%
“…Tholymis tillarga was added to the Dhofar and Oman lists by Ball (2014), with a record of a male and an ovipositing female in Wadi Sayq, which is close to the Yemeni border, though no ID evidence was presented. Lambret et al (2017) recorded T. tillarga, a record of two individuals on 11 November 2010, at a different site from Ball's (2014), but presented no evidence except "observed at close distance". T. tillarga is apparently a migrant (Lambret et al 2017), occurs in India and Africa, and is crepuscular (Subramanian 2009, Djikstra & Clausnitzer 2014 in the adjacent stream in spite of visible pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schneider & Dumont (1997 presented their new records, listed all odonate specimens in the holdings of the Oman Natural History Museum (Muscat), and gave an annotated checklist of the 40 species of odonates then known for Oman. Four more species have been identified from Oman since then: Ischnura fountaineae, I. nursei and Orthetrum abbotti in the north Franković 2012;Kunz 2015) and Tholymis tillarga in the far south in Dhofar governorate (Ball 2014). Weide & Kalkman (2008) included records (sight, specimens, photos) for northern and central Oman, 14-20 September and3-4 October 2002.…”
Section: Introductionmentioning
confidence: 99%